2018
DOI: 10.1371/journal.pone.0194239
|View full text |Cite
|
Sign up to set email alerts
|

Quality of reporting web-based and non-web-based survey studies: What authors, reviewers and consumers should consider

Abstract: BackgroundSeveral influential aspects of survey research have been under-investigated and there is a lack of guidance on reporting survey studies, especially web-based projects. In this review, we aim to investigate the reporting practices and quality of both web- and non-web-based survey studies to enhance the quality of reporting medical evidence that is derived from survey studies and to maximize the efficiency of its consumption.MethodsReporting practices and quality of 100 random web- and 100 random non-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 31 publications
0
45
0
2
Order By: Relevance
“…This survey conforms to the CHERRIES survey reporting checklist (Eysenbach ) and Turk et al .’s () extension to it. The Departmental Ethics Chair in Language and Cognition at University College London waived approval as the study met the criteria for service evaluation.…”
Section: Methodsmentioning
confidence: 99%
“…This survey conforms to the CHERRIES survey reporting checklist (Eysenbach ) and Turk et al .’s () extension to it. The Departmental Ethics Chair in Language and Cognition at University College London waived approval as the study met the criteria for service evaluation.…”
Section: Methodsmentioning
confidence: 99%
“…Son la base para poder pasar a los siguientes niveles de evidencia, permitiendo así, dar un enfoque integral a la investigación en salud donde no solo se valora la parte cuantitativa del proceso salud-enfermedad, sino que nos permite darle un enfoque más holístico integrando el aspecto biopsicosocial del ser humano. Además, las encuestas son útiles para abordar temas que son difíciles de evaluar; permitiendo construir constructos específicos al tema que se desea investigar 3,4 . Las principales limitaciones de este método son los sesgos de información y de medición que tienen que ver directamente con la elección y elaboración del instrumento, siendo el punto crítico la validez y confiabilidad, las que afectan directamente la generalización de los resultados de este tipo de estudios 5,6 .…”
Section: Introductionunclassified
“…En una investigación realizada por Bennett et al 3 sobre la evaluación de la calidad de informes de encuestas en el área médica, en 117 estudios publicados, se encontró que muchos criterios se reportaron deficientemente: pocos estudios proporcionaron la encuesta o las preguntas centrales (35%), informaron la validez o confiabilidad del instrumento (19%), definieron la tasa de respuesta (25%), discutieron la representatividad de la muestra (11%) o identificaron cómo manejaron los datos faltantes (11%); otros investigaciones encontraron resultados similares 4,7,8 . No se encontraron estudios que evalúen la calidad de los informes de encuestas en el área de Odontología.…”
Section: Introductionunclassified
“…However, patient surveys have often been criticised for the lack of conceptual and methodological rigor [19]. Poorly designed surveys and inadequate reporting can lead to inappropriate application of research ndings in decision-making, healthcare, health policy and future research [19][20][21]. To overcome this, quality checklists and reporting guidelines have been developed in order to promote complete and transparent reporting among researchers and to indirectly improve the comprehensiveness and credibility of survey studies [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The checklists include the SUrvey Reporting GuidelinE (SURGE) for paper-based surveys [25] and the CHEcklist for Reporting Results of Internet E-Surveys (CHERRIES) for web-based surveys [26]. Despite the development of guidance for reporting of surveys nearly a decade ago, previous reviews of published survey research have found that key quality criteria relating to design, conduct and results were underreported in the majority of studies [19,20]. In addition, there is limited empirical evidence for optimal survey design [27,28].…”
Section: Introductionmentioning
confidence: 99%